Dinamica de la oviposicion en gansas reproductoras - Ramos, M.=700 1 Murciano, Y.; Pulido, M.; Silva, M.; Fuentes, D.
(En, Es)
Ilus., 17 ref.
Keywords: AVES DE CORRAL; GANSO; REPRODUCCION; OVIPOSICION; CUBA; GANSAS; REVISTA CUBANA DE CIENCIA AVICOLA